Translating the “Banana Genome” to Delineate Stress Resistance, Dwarfing, Parthenocarpy and Mechanisms of Fruit Ripening - Dash, Prasanta K.; Rai, Rhitu (Frontiers in Plant Science, 2016)
Evolutionary frozen, genetically sterile and globally iconic fruit “Banana” entered the genomics era with decoding of structural genome of double haploid Pahang (AA genome constitution) genotype of M. acuminata. This wonder crop, as of today, remains untouched by the green revolution and researchers face intrinsic impediments for varietal improvement to enhance its yield. The complex genome of banana was decoded by hybrid sequencing strategies revealed panoply of genes and transcription factors involved in the process of sucrose conversion that imparts sweetness to its fruit. Banana has historically faced the wrath of pandemic bacterial, fungal and viral diseases and multitude of abiotic stresses that has ruined the livelihood of small and marginal farmers’ and destroyed commercial plantations. Decoding of its structural genome has given impetus to a deeper understanding of the repertoire of genes involved in disease resistance, understanding the mechanism of dwarfing to develop an ideal plant type, unravelling the process of parthenocarpy for better fruit quality, and fruit ripening in this climacteric fruit. Injunction of comparative genomics research will usher in to integrate information from its decoded genome and other monocots into field applications in banana related but not limited to yield enhancement, food security, livelihood assurance, and energy sustainability. In this mini review, we discuss pre- and post-genomic discoveries and highlight accomplishments in structural genomics, genetic engineering and forward genetic accomplishments with an aim to target genes and transcription factors for translational research in banana.